2011
DOI: 10.1111/j.1468-0378.2010.00447.x
|View full text |Cite
|
Sign up to set email alerts
|

602 and One Dead: On Contribution to Global Poverty and Liability to Defensive Force

Abstract: When suggesting that we—the affluent in the developed world—are legitimate targets of defensive force due to our contribution to global poverty one is likely to be countered by one of two strategies. The first denies that we contribute to global poverty. The second seems to affirm that we contribute, and even that we have stringent contribution‐based duties to address this poverty, but denies that such contribution makes forcible resistance permissible. Those in this second group employ several argumentative s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…Finally, the third response to Räikkä’s criticism denies that liability implies culpability (cf. Øverland, 2011: 289). This response has considerable force for reasons offered by Jeff McMahan.…”
Section: Against Moral Equivalence (2): Culpabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, the third response to Räikkä’s criticism denies that liability implies culpability (cf. Øverland, 2011: 289). This response has considerable force for reasons offered by Jeff McMahan.…”
Section: Against Moral Equivalence (2): Culpabilitymentioning
confidence: 99%
“…First, appealing to Barry and Øverland to resist the conclusions of my three analogy arguments comes at a very high price to those who are attracted to Pogge’s analysis of global poverty; for its core claim to being interesting is its contention that rich people violate the negative rights of poor people in ways that, morally speaking, are tantamount to doing harm (cf. Øverland, 2011: 280). 18 Endorsing the Barry and Øverland analysis implies giving up on this claim and, thus, rejecting Pogge’s basis for moral condemnation of how rich people’s treatment of the global poor is seriously, morally wrong.…”
Section: Against Moral Equivalence (3): Doing/allowing Harmmentioning
confidence: 99%
See 1 more Smart Citation
“…Caney (2005) concluded that military intervention is permissible just in case it improves the net satisfaction of basic human rights. Others defended, at least in principle, "redistributive" wars, fought against the global rich to redress the suffering of the global poor (Luban 1980b, Fabre 2012, Lippert-Rasmussen 2013, Øverland 2013.…”
Section: Jus Ad Bellummentioning
confidence: 99%
“…Nonetheless, some philosophers have recently tried to defend redistributive wars. According to Gerhard Øverland, Cécile Fabre, Kasper Lippert-Rasmussen and Gwilym David Blunt, violating duties of global justice can be a just cause for war (Luban, 1980;Øverland, 2011;Fabre, 2012;Lippert-Rasmussen, 2013Barry & Øverland, 2016). They defend the controversial claim that, under certain circumstances and as an ultimum remedium, the global poor can be justified in waging a redistributive war against the global rich.…”
Section: Introductionmentioning
confidence: 99%